1985
DOI: 10.7164/antibiotics.38.427
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of leptomycin B.

Abstract: Leptomycin B was first reported by HAMAMOTO et a!. as an antifungal antibiotic, and showed remarkable cytotoxicity on mammalian cells').

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…LMB, which is an unsaturated, branched-chain fatty acid originally found as an anti-fungal substance (Hamamoto et al, 1983a, b), has also been reported to suppress cell proliferation (Komiyama et al, 1985;Yoshida et al, 1990) and a phase I trial of LMB therapy was performed in patients with malignant tumors (Newlands et al, 1996). The primary side-effects at that time were reported to be nausea and anorexia during systemic treatment (Newlands et al, 1996).…”
Section: Il-1a Into Their Active Forms (Mccawley and Matrisianmentioning
confidence: 96%
See 1 more Smart Citation
“…LMB, which is an unsaturated, branched-chain fatty acid originally found as an anti-fungal substance (Hamamoto et al, 1983a, b), has also been reported to suppress cell proliferation (Komiyama et al, 1985;Yoshida et al, 1990) and a phase I trial of LMB therapy was performed in patients with malignant tumors (Newlands et al, 1996). The primary side-effects at that time were reported to be nausea and anorexia during systemic treatment (Newlands et al, 1996).…”
Section: Il-1a Into Their Active Forms (Mccawley and Matrisianmentioning
confidence: 96%
“…Thus, LMB is considered to potentially function in vivo and might exert many different biological effects. But the role of LMB in the actual metabolism of the extracellular matrix has not yet been elucidated, although it has been reported to potentially inhibit the proliferation of tumor cells (Komiyama et al, 1985;Yoshida et al, 1990). We speculated that LMB could influence the induction of MMP-9 expression, which is controlled by many gene-regulatory elements.…”
mentioning
confidence: 96%
“…As suggested by their rev-like leucine-rich repeats, coimmunoprecipitation experiments demonstrated that pp32 and APRIL interact with the nuclear export factor CRM1. Accordingly, inhibition of CRM1 with the antifungal and antitumor agent leptomycin B (LMB; [102][103][104]) resulted in the loss of shuttling and nuclear accumulation of pp32 and APRIL. Most important, CRM1 inhibition produced increased association of HuR with pp32 and with APRIL, and an increase in HuR's ability to bind nuclear poly(A) + RNA in vivo.…”
Section: Review Articlementioning
confidence: 99%
“…The ability of LMB to sensitize NIH3T3 cells to radiation-induced apoptosis suggests that this fungal metabolite may find use as an anticancer agent in conjunction with other apoptosis-inducing stimuli. LMB1 has antitumor activity against some solid tumors xenografted into mice, 35 but it has yet to be tried in vivo with radiation or chemotherapeutic drugs. Because cyclin B1 is critical in controlling the mitosis in normal cells, LMB is likely to have some toxicity in normal cells, a characteristic that LMB would share with other chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%